STUDYING CORRUPTION AND ANTICORRUPTION IN A LATE MEDIEVAL COMMUNE: THE CASE OF THIRTEENTH-AND FOURTEENTH-CENTURY BOLOGNA. - LOSS, EDWARD (Imago Temporis. Medium Aevum, 2023)
This paper explores the historical meaning of corruption and its forms of contrast in late medieval Bologna. It focuses on understanding the different and changing notions this form of classifiable crime, performed by public officers, assumed in the three main statutes produced in the city between the late Thirteenth and early Fourteenth century: the statutes of 1250-1267, of 1288 and of 1335. Apart from providing a detailed account of all the different actions considered as corruptio in these normative texts, the paper goes further, comparing these dispositions with documents that can offer insights into the practical aspects of the phenomenon, such as chronicles and legal cases. pertaining to the ad maleficia courts